2015
DOI: 10.2174/1874070701509010076
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a Ceramic Carrier after Wastewater Treatment Process in the Model Column Cascade with Ethanol Addition

Abstract: Nitrogen and phosphorus removal from wastewater remains one of the serious environmental problems worldwide. The present study was aimed at combining the both nitrification and phosphorus accumulation processes in the laboratory-scale model system. Synthetic wastewaters (28 mg N-NH 4 + L -1 ) were treated consequently in the cascade of three columns, which were designed for nitrification and phosphorus accumulation processes, respectively, and were packed with porous ceramic beads. Six treatment cycles of seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…As previously mentioned, in the MBBR, nitrification of digestate was advanced (the concentration of NH -N [27,28,29], it was reported that dissolution of phosphate driven by acidification induced by nitrification could be dominant among other biological and chemical reactions (e.g., uptake by microorganisms). According to the regression coefficients between pH values and concentrations of phosphate and calcium ions in the laboratory beaker experiment, the increases of concentrations were estimated to be 34.0 mg L -1 and 44.7 mg L -1 , respectively, when the pH values decreased from 5.9-6.1 to 4.0-4.2.…”
Section: Resultsmentioning
confidence: 96%
“…As previously mentioned, in the MBBR, nitrification of digestate was advanced (the concentration of NH -N [27,28,29], it was reported that dissolution of phosphate driven by acidification induced by nitrification could be dominant among other biological and chemical reactions (e.g., uptake by microorganisms). According to the regression coefficients between pH values and concentrations of phosphate and calcium ions in the laboratory beaker experiment, the increases of concentrations were estimated to be 34.0 mg L -1 and 44.7 mg L -1 , respectively, when the pH values decreased from 5.9-6.1 to 4.0-4.2.…”
Section: Resultsmentioning
confidence: 96%
“…It is one of the lightweight ceramic building materials, which have been used for producing of lightweight concrete blocks. Expanded clay pellets have been investigated for a purification of wastewater from various pollutants in the environmental technologies [7][8][9][10][11]. Expanded clay pellets produced by one stage technology have black central part, which may contain carbon as a result of special sintering conditions [12,13].…”
Section: Introductionmentioning
confidence: 99%